Platinum(II) complexes of aryl guanidine-like derivatives as potential anticancer agents: between coordination and cyclometallation - Mc Donald, Aidan (My University, 2025)
The preparation of a wide variety of Pt(II) complexes with aryl guanidines and their potential application as anticancer agents have been explored. A relatively facile synthesis of cyclometallated Pt(II) complexes of arylguanidines, preparation of Pt(II) guanidine coordination complexes and an in situ activation of platinum arylguanidine complexes with acetonitrile to create a bidentate aryl iminoguanidine Pt(II) complex were achieved. Cyclometallation methodology was extended to create a water-stable conjugate incorporating two Pt(II) ions and a diaryl bis-guanidine DNA minor groove binder. Several crystal structures were obtained confirming these complexation modes. The cyclometallated Pt(II) complexes were particularly stable to aqueous environments and were tested for Reactive Oxygen Species generation and anticancer activity in a leukaemia cancer cell line.
Keywords: aryl guanidines; cancer; Cyclometallation methodology